Physiological responses in different intensities of resistance exercise – Critical load and the effects of aging process. Issue 12 (18th June 2019) - Arakelian, Vivian Maria; Goulart, Cássia da Luz; Mendes, Renata Gonçalves; Sousa, Nuno Manoel de; Trimer, Renata; Guizilini, Solange; Sampaio, Luciana Maria Malosá; Baldissera, Vilmar; Arena, Ross; Reis, Michel S.; Borghi-Silva, Audrey
ABSTRACT: Aim was to identify critical load (CL) in young and elderly apparently healthy male cohorts. To contrast the metabolic, cardiovascular and perceptual responses on CL according to age. We evaluated 12 young (23 ± 3 years) and 10 elderly (70 ± 2 years) apparently healthy active males, who underwent: (1) 1 repetition maximum (1RM) test on a 45° Leg Press; (2) on different days, three high-intensity resistance exercise constant load tests (60%, 75% and 90% 1RM) until fatigue (Tlim). Absolute values of both the CL asymptote and curvature constant (kg) were significantly lower in elderly subjects ( P < 0.05). In contrast, elderly subjects demonstrated a significantly higher number of repetitions at CL when compared with young subjects ( P < 0.05). As expected, oxygen uptake (VO2 ) and heart rate (HR) during maximal aerobic exercise testing were significantly reduced in older subjects. However, percent-predicted aerobic capacity were higher in older subjects ( P < 0.05). In addition, blood lactate ([La − ]) corrected to Tlim and rating of perceived exertion values were greater in younger subjects at all intensities ( P < 0.05). These findings, despite reduced force production in older subjects, endurance-related parameters are well preserved according to age-adjusted percent-predicted values in apparently healthy males.